How far is too far? Theorising non-conviction-based asset forfeiture. Issue 4 (2nd November 2015) - Hendry, Jennifer; King, Colin
Abstract: Non-conviction-based (NCB) asset forfeiture is a relatively recent addition to law enforcement's armoury in the fight against organised crime in the UK. It allows for criminal assets to be forfeited to the State even in the absence of criminal conviction, the stated objective being to undermine the profit incentive of criminal activity. Until now, NCB asset forfeiture has principally been critiqued from a criminological point of view, specifically concerning the Packer models and the civil/criminal dichotomy – aside from this, however, it remains rather underdeveloped theoretically. This paper addresses this lack of legal theoretical engagement with NCB asset forfeiture by providing an initial contribution from a systems-theoretical perspective. This contribution makes use of systems theory's unique insights to critique the perceived 'failure of law' that gave rise to the NCB approach, and challenges the legitimacy of that approach in terms of procedural rights.